APLIKASI PENGOLAHAN DATA ADMINISTRASI PADA CV. ASSYIFA TEBO - Lucy Simorangkir (JURNAL AKADEMIKA)
Administrative data processing are things that must be considered in detail. Good data processing goods and other administrative data. Data processing of goods either at the time the goods enter, update the data, as well as other related activities. Processing of the correct data will generate valid information. So also the withdrawal by the administration that must be taken seriously. CV. Assyifa is a business engaged in the sale Stationery Office (ATK) and Digital Printing. Company located in the center o f Tebo's airport sales and printing services to public and private agencies and the local community. The price offered is quite commensurate with the quality that CV. Assyifa always crowded. CV. Assyifa encounter obstacles in administrative data processing . During this CV. Assyifa in administrative data processing activities are still using a large book in noting any changes that occur, so that frequent errors in preparing reports. For that we need a Web programming applications to overcome these problems. With the programming language PHP (Personal Home Page) Hypertext Preprocessor and MySQL will create a Web-based application. PHP is a scripting language that can be implanted or inserted into HTML. PHP can be used to build Web applications. MySQL is a software SQL database management system or DBMS (Data Base Management System). With PHP and MySQL usual Dynamic Duo will be the solution in building management applications Web -based administration. So as to facilitate in making the report is good and right, as well as in making a sale can be online and handling several branch stores will also be easier